Ethnicity, gender, social class and achievement gaps at age 16: intersectionality and 'Getting it' for the white working class - Strand, S (Taylor and Francis, 2014)
Perhaps the most prevailing inequalities in educational achievement in England are those associated with socio-economic status (SES), ethnicity or gender. However little research has sought to compare the relative size of these gaps or to explore interactions between these factors. This paper analyses the educational achievement at age 11, 14 and 16 of over 15,000 students from the nationally representative Longitudinal Study of Young People in England (LSYPE). At age 16 the achivement gap associated with social class was twice as large as the biggest ethnic gap and six times as large as the gender gap. However the results indicate that ethnicity, gender and SES do not combine in a simple additive fashion, rather there are substantial interactions particularly between ethnicity and SES and between ethnicity and gender. At age 16 among low SES students all ethnic minority groups achieve significantly better than White British students (except Black Caribbean boys who do not differ from White British boys), but at high SES only Indian students outperform White British students. A similar pattern of results was apparent in terms of progress age 11-16, with White British low SES students and Black Caribbean boys (particularly the more able) making the least progress. Parents' educational aspirations for their child and students' own educational aspirations, academic self concept, frequency of completing homework, truancy and exclusion could account for the minority ethnic advantage at low SES, but conditioning on such factors simultaneously indicates substantial ethnic underachievement at average and high SES. Accounts of educational achievement framed exclusively in terms of social class, ethnicity or gender are insufficient and the results challenge educational researchers to develop more nuanced accounts of educational success or failure.